P031 Management of paediatric sleep problems in primary care: a systematic review. (19th November 2019) - Hornsey, Samantha; Hill, Catherine; Stuart, Beth; Muller, Ingrid; Everitt, Hazel
Abstract : Introduction: Sufficient sleep is important for healthy child development. 1 Behavioural Insomnia (BI) is common 1 and can be treated with behavioural and sleep hygiene interventions. 2 3 As a first point of contact for families, primary care offers opportunities to prevent or identify and address sleep problems at an early stage. A US review 4 suggested that professionals lack training and sleep is rarely discussed. Our review further explores primary care professionals' (PCP) knowledge of BI, perceptions of their role and current practice. Methods: Six databases were searched (MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane Library CENTRAL, Web of Science), using terms for 'sleep', 'child/paediatric', 'primary health care', 'general practitioner' and 'health visitor'. Selection criteria included qualitative and/or quantitative studies of PCPs seeing parents or children presenting with paediatric sleep problems or parents/carers of children presenting in primary care. The focus is PCP attitudes, knowledge, understanding and practice regarding paediatric sleep management in primary care. SH is leading paper screening and data extraction. A second reviewer BS screened 20% of initial titles/abstracts, will screen 20% of full texts and will check data extraction. The mixed methods appraisal tool will be used for quality appraisal. A mixed-methods synthesis will include a thematic synthesis of qualitative papers and a narrative synthesis of quantitative papers. Results: Database searches resulted in 7578 results, de-duplicated to approximately 5500. Approximately 400 papers were included from title/abstract screening for potential eligibility. Full texts are currently being screened for full eligibility and data is being extracted. Results will be presented at the conference. Discussion: A greater understanding of PCP knowledge of BI, perceptions of their role and current practice will identify key areas to inform research to improve the management of paediatric sleep problems in primary care. References: Hill C. Practitioner Review: Effective treatment of behavioural insomnia in children. Journal of Child Psychology and Psychiatry 2011;52(7):731–41. Allen SL Howlett MD Coulombe JA, Corkum PV. ABCs of SLEEPING: A review of the evidence behind pediatric sleep practice recommendations. Sleep Medicine Reviews 2016;29:1–14. Meltzer LJ, Mindell JA. Systematic Review and Meta-Analysis of Behavioral Interventions for Pediatric Insomnia. Journal of Pediatric Psychology 2014;39(8):932–48. Honaker SM, Meltzer LJ. Sleep in pediatric primary care: A review of the literature. Sleep Medicine Reviews 2016;25:31–9.